2018
DOI: 10.5194/soil-4-101-2018
|View full text |Cite
|
Sign up to set email alerts
|

Proximal sensing for soil carbon accounting

Abstract: Abstract. Maintaining or increasing soil organic carbon (C) is vital for securing food production and for mitigating greenhouse gas (GHG) emissions, climate change, and land degradation. Some land management practices in cropping, grazing, horticultural, and mixed farming systems can be used to increase organic C in soil, but to assess their effectiveness, we need accurate and cost-efficient methods for measuring and monitoring the change. To determine the stock of organic C in soil, one requires measurements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 139 publications
(152 reference statements)
0
45
0
1
Order By: Relevance
“…The most frequent statistical indicators are RMSE, RPD, and R 2 . It should be noted that the error should be referred to using the same units as those of the analyzed soil property [146]; most studies do not use the same evaluation methods, as shown in Tables 1 and 2. In addition to that, the normalization of the data due to skewness makes it even harder to compare studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent statistical indicators are RMSE, RPD, and R 2 . It should be noted that the error should be referred to using the same units as those of the analyzed soil property [146]; most studies do not use the same evaluation methods, as shown in Tables 1 and 2. In addition to that, the normalization of the data due to skewness makes it even harder to compare studies.…”
Section: Discussionmentioning
confidence: 99%
“…Standardization of reference laboratory methods, spectral measurements and soil data exchange to some extent negates these issues, and they are addressed in several international co‐operations, one of which is Pillar 5 of the Global Soil Partnership (GSP, ). If standardization and calibration transfer challenges can be solved, combining spectral libraries can provide a vast data resource for not only local but also more regional and global SOC analyses (England & Viscarra Rossel, ; Viscarra Rossel, Behrens, et al, ; Viscarra Rossel, Brus, Lobsey, Shi, & Mclachlan, ).…”
Section: Novel Methods Of Measuring Soc Changementioning
confidence: 99%
“…A method used in a number of set‐ups is gamma attenuation. This can be measured on the extracted soil core (England & Viscarra Rossel, ; Lobsey & Viscarra Rossel, ) or directly in the soil (Jacobs, Eelkema, Limburg, & Winterwerp, ). With this technique, the attenuation by matter of gamma radiation originating from a small radioactive source is measured over a known volume between source and detector.…”
Section: Novel Methods Of Measuring Soc Changementioning
confidence: 99%
“…Certain articles were excluded due to inadequate results justification. Considering Scopus may fail to retrieve a significant percent of related works [56], previous reviews and surveys [7,9,19,27,38,46,54,[57][58][59][60][61][62][63][64][65] were further examined for related work and references from the selected articles were also evaluated, resulting in 28 articles in total.…”
Section: Methodsmentioning
confidence: 99%